Microfluidic Skin‐on‐a‐Chip Models: Toward Biomimetic Artificial Skin. Issue 39 (30th July 2020) - Sutterby, Emily; Thurgood, Peter; Baratchi, Sara; Khoshmanesh, Khashayar; Pirogova, Elena
Abstract: The role of skin in the human body is indispensable, serving as a barrier, moderating homeostatic balance, and representing a pronounced endpoint for cosmetics and pharmaceuticals. Despite the extensive achievements of in vitro skin models, they do not recapitulate the complexity of human skin; thus, there remains a dependence on animal models during preclinical drug trials, resulting in expensive drug development with high failure rates. By imparting a fine control over the microenvironment and inducing relevant mechanical cues, skin‐on‐a‐chip (SoC) models have circumvented the limitations of conventional cell studies. Enhanced barrier properties, vascularization, and improved phenotypic differentiation have been achieved by SoC models; however, the successful inclusion of appendages such as hair follicles and sweat glands and pigmentation relevance have yet to be realized. The present Review collates the progress of SoC platforms with a focus on their fabrication and the incorporation of mechanical cues, sensors, and blood vessels. Abstract : Skin‐on‐a‐chip (SoC) platforms leverage microfluidic technologies to offer fine control over the cellular microenvironment while closely mimicking the structural and functional properties of the human skin. This Review systematically collates and discusses recent progress on SoC development, highlighting the applications of such platforms for studying the response of skin under various stimuli, modeling skin diseases, and drug development.